Normative isokinetic knee strength values and prediction models in non-athletic Chinese adults - Liu, Kun; Yin, Lulu; Zhang, Ye; Liu, Gongliang; Fang, Ping; Ma, Yanhong; Huang, Lihua (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundEstablishing normative isokinetic muscle strength values and prediction models for knee joints in non-athletic healthy Chinese adults aids in clinical assessments, diagnosis, and rehabilitation. However, there has been limited research on these normal reference values, particularly involving large sample cohorts. Therefore, this study aimed to develop normative reference values and predictive models for knee joint isokinetic muscle strength across different age groups and genders in non-athletic healthy Chinese adults.MethodsA total of 2,208 participants aged between 20–70 years old were included in the study. The participants were divided into two groups by gender and further divided into five age groups: 20–29, 30–39, 40–49, 50–59 and 60–69 years old, resulting in a total of 10 groups. Key parameters, including peak torque of knee flexors and extensors, relative peak torque, peak torque ratio of flexors to extensors, peak torque angle and work, were collected using an isokinetic dynamometer at angular velocities of 60°/s and 180°/s. Two-way analysis of variance was utilised to analyse the characteristics and differences of these parameters amongst different age groups and genders. Pearson correlation coefficients were calculated to examine the relationships between these parameters and gender, age, height, weight and body mass index. Predictive models were developed using linear regression and various machine learning techniques.ResultsMales exhibited significantly higher knee isokinetic strength values than females across all age groups, with knee extensor strength 20.47%–38.01% higher and knee flexor strength 22.91%–43.42% higher at both 60°/s and 180°/s. Muscle strength showed a moderate negative correlation with age, indicating a decline with increasing age. Extension strength values were greater than flexion, and measurements at 180°/s were lower compared to 60°/s. The multilayer perceptron regressor demonstrated the highest predictive capability among the models tested.ConclusionThis study provides comprehensive normative reference values and predictive models for knee joint isokinetic muscle strength in non-athletic healthy Chinese adults. The results highlight significant gender and age differences, offering valuable data for clinical assessments and personalized rehabilitation strategies to improve knee joint health and overall quality of life.